Universal health coverage in Latin America? - Asa Cristina Laurell (Social Medicine Publication Group, 2016)
This Medicina Social/Social Medicine issue includes, among others, two articles critical of so-called Universal Health Coverage (UHC), one by Mishra and Seshadri and another by Waitzkin. The debate surrounding UHC has been around for a while in Latin America, where progressive governments have worked towards guaranteeing the universal right to health through a single, free, public health system, whilst neoliberal governments have implemented policies based on public-private insurance schemes and competition between public and private health service providers. The debate therefore swings between two different and opposing perspectives based on different views of the world and society where the competition between public and private insurance forms part of the neoliberal doctrine and the single, free, public health system is linked to the welfare state. The doctrinal and ideological nature of the neoliberal approach is demonstrated by the fact that it is modeled on the most expensive and inefficient health system in the world: that of the US. ...